Paradigma Integratif Filsafat Pendidikan Islam: Sistesis Ontologis, Epistemologis, dan Aksiologis Tokoh Klasik-Kontemporer - Nurdi; Miftahul Huda; Zulfa Aminatuzzahroh (Tarbiyah: Jurnal Pendidikan Agama Islam, 2025)
This study aims to formulate an integrative paradigm within the philosophy of Islamic education by conducting an in-depth analysis of its ontological, epistemological, and axiological constructions from the classical to the contemporary period. Employing a library research method combined with historical–genealogical analysis, textual hermeneutics, and conceptual–comparative examination, the study traces the developmental patterns of major Muslim thinkers and their implications for renewing Islamic education. The findings reveal that the epistemic structure of Islamic education is shaped through the harmonization of revelation, reason, and empirical experience, which collectively underpin a transformative educational model grounded in a tawhidic worldview. The study further formulates the Humanistic–Integrated Model, positioning spirituality, rationality, sociality, and contextuality as core pillars of holistic education. Theoretically, the integrative paradigm strengthens the foundations of Islamic educational philosophy by shifting the discourse from dogmatic orientations toward reflective–critical inquiry. Practically, it offers direction for designing balanced curricula, dialogic and humanistic pedagogical strategies, and an ethical academic culture responsive to global developments. Overall, this research provides a substantive contribution to advancing Islamic educational theory and practice that is relevant, adaptive, and oriented toward the attainment of the public good